2013
DOI: 10.1037/a0029178
|View full text |Cite
|
Sign up to set email alerts
|

Human learning of elemental category structures: Revising the classic result of Shepard, Hovland, and Jenkins (1961).

Abstract: The findings of Shepard, Hovland, and Jenkins (1961) on the relative ease of learning 6 elemental types of 2-way classifications have been deeply influential 2 times over: 1st, as a rebuke to pure stimulus generalization accounts, and again as the leading benchmark for evaluating formal models of human category learning. The litmus test for models is the ability to simulate an observed advantage in learning a category structure based on an exclusive-or (XOR) rule over 2 relevant dimensions (Type II) relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(103 citation statements)
references
References 62 publications
4
99
0
Order By: Relevance
“…A similar result was reported by Love (2002) [45] who found only a marginal Type II advantage compared to the Type IV problem in a related design. In a series of experiments, Kurtz et al [47] have argued that the Type II advantage can be explained by the extent to which instructions emphasize verbal rules.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was reported by Love (2002) [45] who found only a marginal Type II advantage compared to the Type IV problem in a related design. In a series of experiments, Kurtz et al [47] have argued that the Type II advantage can be explained by the extent to which instructions emphasize verbal rules.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we were inspired to seriously question the most surprising finding in the traditional SHJ (Shepard, Hovland, & Jenkins) ordering: the tremendous ease with which learners acquire a nonlinearly separable and seemingly unnatural category structure in Type IIthe XOR rule that requires learners to separate, for example, white squares and black triangles from white triangles and black squares. In a series of behavioral studies (Kurtz, Levering, Stanton, Romero, & Morris, 2013), we found compelling evidence that the classic ordering actually depends on the inclusion of task instructions that encourage rule formation. Specifically, Type II is not significantly faster than Type IV under neutral instructions, but it is learned more quickly when the experimental task explicitly encourages hypothesis testing or selective attention.…”
Section: Challenging the Reference Point Account Of Taclmentioning
confidence: 88%
“…One possible explanation of this result within the framework of Combination Theory is that incidental conditions promote simple additive combination rules (all that is required for Type IV) over more esoteric combination rules, such as exclusive-or. However, given a recent report that, even under intentional conditions, Type IV is sometimes easier than Type II (Kurtz et al, 2013), further research is probably required.…”
Section: Limitations and Extensionsmentioning
confidence: 99%